2020
DOI: 10.1016/j.drugpo.2019.102625
|View full text |Cite
|
Sign up to set email alerts
|

Estimated effect of US state syringe sale policy on source of last-used injection equipment

Abstract: Background: Many people who inject drugs (PWID) lack access to a new sterile syringe each time they inject, with increased risk of injection-related harms, including spread of communicable diseases. In the United States (US), restricted access is largely due to state laws and policies regulating syringe access. Our aim in this US-focused study is to estimate variations in syringe acquisition behavior in relation to state-level syringe sale policies, drawing upon self-identified PWID in a nationally representat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…[ 46 ] Further, some states have regulations that make it difficult for syringes to be mailed, such as requiring onsite HIV and HCV testing, or limiting distribution to officially designated geographic areas [ 45 ]. In contrast, unrestrictive syringe policies are associated with increased acquisition of sterile syringe supplies [ 47 ]. For mail-delivery to be broadly expanded, participants must have confidence that they will not face prosecution or penalties for using these services.…”
Section: Legal Landscape Of Mail-order Servicesmentioning
confidence: 99%
“…[ 46 ] Further, some states have regulations that make it difficult for syringes to be mailed, such as requiring onsite HIV and HCV testing, or limiting distribution to officially designated geographic areas [ 45 ]. In contrast, unrestrictive syringe policies are associated with increased acquisition of sterile syringe supplies [ 47 ]. For mail-delivery to be broadly expanded, participants must have confidence that they will not face prosecution or penalties for using these services.…”
Section: Legal Landscape Of Mail-order Servicesmentioning
confidence: 99%
“…5 Data analyzed from the National Survey on Drug Use and Health (2002 to 2011) showed that in states with unrestricted syringe retail sale policies, 66.3% of people who injected drugs reported their last syringe source was a pharmacy, compared with 45.9% in states restricting sales. 6 Removing legal barriers to retail sale of syringes and needles may not be sufficient because sales decisions are often left to a pharmacist's discretion, even in states allowing unrestricted sales. People who inject drugs commonly report feeling judged by pharmacy staff and being refused nonprescription purchase of injection supplies.…”
Section: Improving Access To Sterile Injection Suppliesmentioning
confidence: 99%
“…In 2017, at least 28 states had drug paraphernalia laws that referred to syringes or needles. 6 Such laws may deter people who inject drugs from visiting pharmacies to pur-chase supplies, even if these sales are permitted. Excluding procurement of sterile injection supplies at pharmacies from these laws might decrease fears of legal repercussions around such sales and increase the likelihood that people who inject drugs will obtain sterile injection supplies.…”
Section: Improving Access To Sterile Injection Suppliesmentioning
confidence: 99%
See 2 more Smart Citations